Extreme Sports, Extreme Bodies Gender, Identities and Bodies in Motion - Andreasson, Jesper; Johansson, Thomas; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2019)
This book investigates extreme sports, defined as sports in which athletes challenge and transgress societal perceptions of what is humanly possible to achieve, in terms of physical training and bodily development/performance. Situated within a growing body of literature analysing the impact of new training trends on an individual's body, identity, lifestyle and perception of his/her social surroundings, Extreme Sports, Extreme Bodies focuses on the gendered and embodied experiences of bodybuilding, Ironman triathlon, and mixed martial arts. Through their ethnographic analysis, Andreasson and Johansson present a unique and updated account of the increasing phenomenon of extreme sports and extreme bodies in contemporary Western society, grounded in the sociology of sport, body studies and embodiment literature.
Part I: Introducing Extreme Sporting Bodies -- Chapter One: Introduction -- Chapter Two: Body Studies and Carnal Sociology -- Part II: Bodybuilding and the Fitness Revolution -- Chapter Three: Getting the Pump - Pain and Pleasure in Muscle-building Practice -- Chapter Four: Negotiating the Subcultural body -- Chapter Five: Bodybuilding - Concluding Thoughts. - Part III: Bending Bodies Through Ironman Triathlon -- Chapter Six: Discipline, Transcendence and Bodily Fluids -- Chapter Seven: The Family Puzzle in Ironman Triathlon. - Chapter Eight: Ironman - Concluding Thoughts. Part IV: Mixed Martial Arts and Spectacular Bodies -- Chapter Nine: Fists, Blood and Emotions -- Chapter Ten: (Re)Negotiating Violence. - Chapter Eleven: MMA - Concluding Thoughts -- Part V: Theorising Extreme Bodies -- Chapter Twelve: Bodies in Theory and Practice -- Appendix: Research Design and Methodology.
Keywords: Sports -- Sociological aspects; Sex; Sport Sociology; Gender Studies